Tik-Tok Use and Its Impact on Student Interaction: A Qualitative Study of Senior High School Students in Jambi, Indonesia - Anisatun Indriyani; Firdaus Firdaus; Elvawati Elvawati (Indonesian Journal of Religion and Society, 2025)
The rapid expansion of social media has fundamentally transformed adolescents’ social interactions, positioning digital platforms as integral elements of everyday life. This study examines patterns of TikTok use among senior high school students and analyzes its implications for their social interaction practices. Drawing on Manuel Castells’ theory of the network society, this research adopts a qualitative descriptive approach conducted at SMA Negeri 5 Tebo, Jambi Province, Indonesia. Data were collected through in-depth interviews with twelve informants, non-participant observation, and document analysis, and were analyzed using the Miles and Huberman interactive model. The findings reveal that students spend between one and five hours per day on TikTok, accessing the platform across various times and locations. TikTok facilitates the expansion of students’ social networks and provides spaces for self-expression and peer connectivity. However, intensive engagement with the platform also contributes to a decline in face-to-face interaction and fosters tendencies toward social withdrawal, which may affect students’ communication skills and the quality of interpersonal relationships. This study highlights the dual role of TikTok as both an enabling and constraining force in students’ social lives. Balanced guidance and contextual supervision are therefore essential to maximize the social benefits of social media while mitigating its potential risks